2018
DOI: 10.1002/ijch.201700074
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Migration of Propargyl Acetate as an Entry into the Total Synthesis of Natural Products

Abstract: Gold catalysis has emerged over the last two decades as a protocole of choice for the efficient and selective activation of a variety of organic functional groups. This has served to the total synthesis of natural products at several occasions. In this context, the gold‐catalyzed migration (1,2‐ or 1,3‐) of propargyl acetates has been particularly used. This review highlights these different synthetic developments which are presented according to the involved mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Malacria, Fensterbank, and Gandon and their co-workers studied experimentally and computationally the Au-catalyzed cycloisomerizations of related substrate classes, namely, 1,3-enynes and allenynes carrying a propargylic ester group. , They developed an efficient preparation of polycyclic compounds 334 (Scheme , top), which was applied in total synthesis. , In order to suppress the formation of cyclopentadiene side products, the internal position of the 1,3-enyne framework had to be substituted (group R in Scheme , bottom). Several mechanistic pathways were computed, and the lowest energy one was found to proceed through [3,3]-sigmatropic rearrangement of propargyl acetates 333 into allenyl acetates 335 , followed by metalla-Nazarov reaction of gold complex 337 .…”
Section: Construction Of 3-membered Rings Catalyzed By Goldmentioning
confidence: 99%
See 1 more Smart Citation
“…Malacria, Fensterbank, and Gandon and their co-workers studied experimentally and computationally the Au-catalyzed cycloisomerizations of related substrate classes, namely, 1,3-enynes and allenynes carrying a propargylic ester group. , They developed an efficient preparation of polycyclic compounds 334 (Scheme , top), which was applied in total synthesis. , In order to suppress the formation of cyclopentadiene side products, the internal position of the 1,3-enyne framework had to be substituted (group R in Scheme , bottom). Several mechanistic pathways were computed, and the lowest energy one was found to proceed through [3,3]-sigmatropic rearrangement of propargyl acetates 333 into allenyl acetates 335 , followed by metalla-Nazarov reaction of gold complex 337 .…”
Section: Construction Of 3-membered Rings Catalyzed By Goldmentioning
confidence: 99%
“…In 1987, the first homogeneous gold-catalyzed addition of nucleophiles to alkynes was realized by the group of Utimoto using sodium tetrachloroaurate dihydrate. , One decade later, Teles et al and Tanaka et al demonstrated the possibility of activating alkynes using gold­(I) complexes. From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…The unique alkynophilicity of cationic gold(I) catalysts has been exploited as a powerful tool to construct structurally complex molecular frameworks, which otherwise represent difficult synthetic challenges. [1] In many cases, gold(I) catalysis has successfully offered synthetic access to natural product-based [2] or -inspired small molecules. [3] Mechanistically, the electrophilic character of alkyne substrates (1) is enhanced when the cationic gold(I) catalyst first coordinates the acetylene moiety (2) followed by nucleophilic addition to the ensuing gold(I)-acetylene complexes (2).…”
Section: Introductionmentioning
confidence: 99%
“…[1] In many cases, gold(I) catalysis has successfully offered synthetic access to natural product-based [2] or -inspired small molecules. [3] Mechanistically, the electrophilic character of alkyne substrates (1) is enhanced when the cationic gold(I) catalyst first coordinates the acetylene moiety (2) followed by nucleophilic addition to the ensuing gold(I)-acetylene complexes (2). Often, this addition further triggers a range of different transformations through cascade type reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation